Switching from zidovudine/lamivudine to tenofovir/emtricitabine improves fat distribution as measured by fat mass ratio. Issue 6 (11th December 2014) - Martínez, E; Ribera, E; Clotet, B; Estrada, V; Sanz, J; Berenguer, J; Rubio, R; Pulido, F; Larrousse, M; Curran, A; Negredo, E; Arterburn, S; et al.
<x xml:space="preserve">Abstract</x> Objectives Fat mass ratio (FMR) has been suggested as an objective indicator of abnormal body fat distribution in HIV infection. Although it could provide more comprehensive information on body fat changes than limb fat mass, FMR has scarcely been used in clinical trials examining body fat distribution in HIV‐infected patients. Methods A subanalysis of a controlled, randomized clinical trial in virologically suppressed HIV‐1‐infected men switching from zidovudine (ZDV)/lamivudine (3TC) to emtricitabine (FTC)/tenofovir (TDF) versus continuing on ZDV/3TC was carried out. FMR was assessed by dual X‐ray absorptiometry (DEXA) for a period of 72 weeks. Lipoatrophy was defined as FMR ≥ 1.5. Multivariate linear regression models for the change in FMR from baseline were fitted. Results Sixty‐five men were randomized and treated (28 in the FTC/TDF arm and 37 in the ZDV/3TC arm), and 57 completed the study (25 and 32 in each arm, respectively). In the FTC/TDF arm, adjusted mean FMR decreased by 0.52 at week 72 (P = 0.014), and in the ZDV/3TC arm it increased by 0.13 (P = 0.491; P between arms = 0.023). Among subjects with lipoatrophy (baseline FMR ≥ 1.5), adjusted FMR decreased by 0.76 (P = 0.003) in the FTC/TDF arm and increased by 0.21 (P = 0.411; P between arms = 0.009) in the ZDV/3TC arm. Baseline FMR and treatment group were significant predictors (P < 0.05) of post‐baseline changes in FMR. Conclusions Switching from ZDV/3TC to FTC/TDF led to an improvement in FMR, compared with progressive worsening of FMR in subjects receiving ZDV/3TC, showing that fat mass not only increased but was also distributed in a healthier way after the switch.